The merry adventures of Robin Hood - Pyle, Howard, 1853-1911 (Boston, Mass : Thomson Heinle, 2007)
Recounts the legend of Robin Hood, who plundered the king's purse and poached his deer and whose generosity endeared him to the poor
Keywords: American literature; Robin Hood (Legendary character) -- Legends; Folklore -- England